Pengaruh Word of Mouth, Product Quality Aplikasi Shopee terhadap Purchase Intention dengan Brand Image Sebagai Variabel Intervening - Fiki Praditya Arnanda (Universitas Batanghari Jambi, 2022)
This study aims to determine the effect of Word Of Mouth (WOM), Product Quality (PQ), Brand Image (BI) on Purchase Intention (PI) on the Shopee application. The data collection technique uses a non-probability sampling method, which is a data or sample collection technique so that all data may not be selected as a sample of the same size. Based on the policy of the researcher in determining the sample elements to be used. In this non-probability sampling, the element to be used has an uncertain nature. This research is a type of quantitative research and uses primary data. The data analysis method used multiple linear regression analysis using SPSS version 23. The results of this study indicate that Word of Mouth (WOM) has a positive and significant effect on Purchase Intention (PI). Product Quality (PQ) has no significant positive effect on Purchase Intention (PI). Brand Image (BI) has a positive and significant effect on Purchase Intention (PI). The effect of Word Of Mouth (WOM) on Purchase Intention (PI) through Brand Image (BI) as an intervening variable is accepted. The effect of Product Quality (PQ) on Purchase Intention (PI) through Brand Image (BI) as an intervening variable is accepted.